Edwards, Germany, and transatlantic contexts - Bezzant, Rhys S. (New directions in Jonathan Edwards studies, 2022)
"Jonathan Edwards engaged in notable ways with the church in Germany through his writings on spirituality, theology and missiology, but this contribution has rarely been acknowledged in academic publications. In this book scholars who have an interest in both Edwards and the church in Europe offer contributions to a significant worldwide conversation on Edwards's texts and teachings. He found an ally in Martin Luther, sought out encouragement from German Pietists, and engaged with Western traditions of philosophy which proved useful in sharpening subsequent reflection on God's work in the world. Edwards was not just a remote colonial American pastor, but an active participant in the transatlantic republic of letters and contributed to the birth of the global missions movement, for which the church in Germany was itself a significant base." --Provided by publisher
Keywords: Edwards, Jonathan -- 1703-1758; Europe -- Church history; United States -- Church history; Aufsatzsammlung; Erweckungsbewegung; Protestantismus; Deutschland; Rezeption; Edwards, Jonathan; Geschichte; Philosophie; Frömmigkeit